Land use dynamics and policy implications in Central China: A case study of Zhengzhou. (October 2016) - Mu, Bo; Mayer, Audrey L.; He, Ruizhen; Tian, Guohang
Abstract: The decisions of the central Chinese government have been a key driver of the urbanization process in large cities in eastern China, however their influence on the later-urbanizing cities in central China is unclear. The objective of this study was to use remote sensing data and spatial metrics to identify the relative influence of planning policies at various levels (relative to socioeconomic influences) on trends in landscape patterns in the rapid urbanization process of Zhengzhou, the capital city of Henan Province and the core city of central China. Our results revealed that Zhengzhou's rapid urbanization process started about a decade after the eastern coastal cities due to the national development strategy (the Preferential Regional Development Strategy in 1980s and the Hinterland City Opening Policy in 1992), but boomed after 2000 due to increasing national support along with an increased number of planning policies at multiple levels. After 2004, the city experienced a critical landscape transition from a primarily agricultural to an urban-dominated landscape (which has not yet occurred over the whole region). Planning for an inter-city railway network and construction between cities increased the connectivity of urban space, but fragmented other land use types. Urban and green space expanded primarily into agricultural areas, reducing them in extent, simplifying their boundaries, and increasing their fragmentation; these changes likely reduce food production capacity. Trends in construction sites illustrate the exhaustion of land resources in Zhengzhou city and forecast a new round of urban growth in the adjacent cities (Xinzheng, Zhongmou and Xingyang). High-level policy intervention and scientific planning will be very important to urban-rural sustainable development for the region. Highlights: Urban land use was the largest consumer of land resources while agriculture was the largest contributor National and local planning policy played a primary role in shaping landscape patterns relative to socioeconomic factors Remote sensing technology and landscape ecology should have a fundamental influence on planning policy